Imaging Correlate to the Pathophysiology and Natural History of Alcohol Related Pancreatitis - Maheshwari, Sharad; Patel, Zilka; Khatib, Ahmed; Kumar, Sachin; Mehta, Gaurav; Harisinghani, Mukesh (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Alcohol-induced pancreatitis (ALP) presents a growing health concern, with recent rising prevalence. According to the National Institute on Alcohol Abuse and Alcoholism, alcohol abuse is indeed a leading cause of both acute and chronic pancreatitis in the United States. A study found that alcohol accounted for nearly one-third of acute pancreatitis cases in the United States. The impact of ALP extends a substantial burden on health care systems due to the need for medical interventions, hospitalizations, and long-term management of chronic conditions. Binge drinking and high-intensity drinking, characterized by consuming large amounts of alcohol in a short period or engaging in heavy drinking episodes, respectively, exacerbate the risk of pancreatitis and complicate its management.While the imaging characteristics of ALP may not differ significantly from other common causes of pancreatitis, such as gallstones, identifying its unique natural history and pathophysiology is essential for accurate diagnosis and management. By leveraging the capabilities of various imaging modalities and by being aware of the unique features, radiologists can contribute to the clinical management of this condition. This is a comprehensive review of the pathophysiology, natural history, and imaging of ALP for radiologists to enhance their understanding and diagnostic accuracy.
Keywords: alcohol-induced pancreatitis; alcoholic pancreatitis; binge pancreatitis; fatty acid ethyl esters; high-intensity drinking; pancreatic stellate cells